Structural, magnetic and specific heat studies of Bi1−xLaxMn2O5 (x=0, 0.1, 0.2 and 0.3) multiferroics. (December 2016) - Sagar, E.; Kumar, N. Pavan; Reddy, P. Venugopal
Abstract: A series of multiferroic materials with the compositional formula Bi1−x Lax Mn2 O5 (x=0, 0.1, 0.2 and 0.3) in single phase were prepared by the solid state reaction technique. After characterizing the samples structurally, a systematic investigation of specific heat and magnetization studies were carried out over the temperature range, 2–300 K. Based on these studies, it has been observed that the magnetization versus temperature plots of all the samples are found to split in the ZFC and FC modes and the observed behavior is explained on the basis of magnetic inhomogeneity. Finally, using the specific heat data, the magnetic entropy values were calculated using Einstein model. Highlights: The Antiferromagnetic transition temperatures are decreasing with increasing doping concentration. Magnetic entropy is computed using heat capacity data. Magnetic entropy values are found to decrease with doping concentration.